Genetic population of Plasmodium knowlesi during pre-malaria elimination in Thailand - Sugaram, R; Boondej, P; Srisutham, S; Kunasol, C; Pagornrat, W; Boonyuen, U; Dondorp, AM; Saejeng, A; Sudathip, P; Imwong, M (BioMed Central, 2021)
Background Thailand is committed to eliminating malaria by 2024. From 2013 to 2020, the total number of malaria cases have decreased, from 37,741 to 4474 (an 88.1% reduction). However, infections with Plasmodium knowlesi, a monkey malarial pathogen that can also infect humans, have been increasingly observed. This study focused on the molecular analysis of P. knowlesi parasites causing malaria in Thailand. Methods Under Thailand’s integrated Drug Efficacy Surveillance (iDES), which includes drug-resistance monitoring as part of routine case-based surveillance and responses, specimens were collected from malaria patients (n = 966) between 2018 and 2020. Thirty-one mono P. knowlesi infections (3.1%), most of which were from eastern and southern Thailand, were observed and confirmed by nested PCR assay and DNA sequencing. To evaluate whether these pathogens were from different lineages, cluster analysis based on seven microsatellite genotyping markers and the merozoite surface protein 1 (pkmsp1) gene was carried out. The P. knowlesi pyrimethamine resistance gene dihydrofolate reductase (pkdhfr) was sequenced and homology modelling was constructed. Results The results of analysing the seven microsatellite markers and pkmsp1 sequence demonstrated that P. knowlesi parasites from eastern Thailand were of the same lineage as those isolated in Cambodia, while the parasites causing malaria in southern Thailand were the same lineage as those isolated from Malaysia. The sequencing results for the pkdhfr genes indicated the presence of two mutations, Arg34Leu and a deletion at position 105. On analysis with homology modelling, the two mutations were not associated with anti-malarial drug resistance. Conclusions This report compared the genetic populations of P. knowlesi parasites in Thailand from 2018 to 2020 and have shown similar lineages as those isolated in Cambodia and Malaysia of P. knowlesi infection in Thailand and demonstrated that the P. knowlesi parasites were of the same lineages as those isolated in Cambodia and Malaysia. The parasites were also shown to be sensitive to pyrimethamine.